About a pure soul, a teacher and a friend (to the memory of A.S. Zinovyev) - G. B. Fyodorova (Бюллетень сибирской медицины)
In 2003 went away from life Anton S. Zinovyev corresponding member of the Academy of Medical Science of Russia, Honoured Scientist of the Russian Federation, Professor. In the paper author makes an attempt to show the personality of famous Russian scientist-pathological anatomist.